An Effective Method for Acute Vagus Nerve Stimulation in Experimental Inflammation - Caravaca, April S.; Gallina, Alessandro L.; Tarnawski, Laura; Tracey, Kevin J.; Pavlov, Valentin A.; Levine, Yaakov A.; Olofsson, Peder S. (Frontiers in Neuroscience, 2019)
Neural reflexes regulate inflammation and electrical activation of the vagus nerve reduces inflammation in models of inflammatory disease. These discoveries have generated an increasing interest in targeted neurostimulation as treatment for chronic inflammatory diseases. Data from the first clinical trials that use vagus nerve stimulation (VNS) in treatment of rheumatoid arthritis and Crohn’s disease suggest that there is a therapeutic potential of electrical VNS in diseases characterized by excessive inflammation. Accordingly, there is an interest to further explore the molecular mechanisms and therapeutic potential of electrical VNS in a range of experimental settings and available genetic mouse models of disease. Here, we describe a method for electrical VNS in experimental inflammation in mice.